KEPEMIMPINAN SPIRITUAL PADA PESANTREN MAHASISWA (Studi Multsitus pada Pesantren Mahasiswa Ulul Albab, Ulul Yaqin dan Ulul Hikam Malang) - julianto, endri (J-MPI (Jurnal Manajemen Pendidikan Islam), 2016)
Spiritual leaders are leaders who influence people led by inspired, enlighten, awaken, enabling, and empowering through the approach of spirituality or religious ethical values. This research was conducted in three boarding students, in student boarding Ulul Albab, Ulul Yaqin and Ulul Hikam in Malang, East Java, using a qualitative approach. This study was designed wearing a multi-site study. Once the data as a whole has finished checking, the data collected were analyzed, with analysis of the site as well as inter-site analysis. From the research result shows that: (1) Perspective spiritual leadership is a boarding student. (2)Spirituality actualization of leadership in the assembly caregivers (3) Typology of leadership tends to behavior leadership of participative colleguelike – democratic - spiritual religion (4) Decision-making (5) Settlement of individual conflicts (6) The development team (7) Variety of spiritual leadership in organizational culture (8) The value system of spiritual leadership, and (9) There are several obstacles and solutions in spiritual leadership at the boarding (pesantren) students.